Fundamentals in Covid-19-Associated Thrombosis: Molecular and Cellular Aspects - Mizurini, Daniella M.; Hottz, Eugenio D.; Bozza, Patrícia T.; Monteiro, Robson Q. (Frontiers in Cardiovascular Medicine, 2021)
The novel coronavirus disease (COVID-19) is associated with a high incidence of coagulopathy and venous thromboembolism that may contribute to the worsening of the clinical outcome in affected patients. Marked increased D-dimer levels are the most common laboratory finding and have been repeatedly reported in critically ill COVID-19 patients. The infection caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is followed by a massive release of pro-inflammatory cytokines, which mediate the activation of endothelial cells, platelets, monocytes, and neutrophils in the vasculature. In this context, COVID-19-associated thrombosis is a complex process that seems to engage vascular cells along with soluble plasma factors, including the coagulation cascade, and complement system that contribute to the establishment of the prothrombotic state. In this review, we summarize the main findings concerning the cellular mechanisms proposed for the establishment of COVID-19-associated thrombosis.